Truth commission impact: an assessment of how commissions influence politics and society - Bakiner, Onur (International journal of transitional justice, 2014)
This article explains whether or not, and the specific ways in which, truth commissions established during a political transition in fact transform lessons from history into political and judicial impact, defined as influence on government policy and judicial processes. It isolates impact from the causal effects of similar postconflict institution building and other transitional justice and conflict resolution measures. Drawing upon the existing literature, it examines several causal mechanisms through which commissions are expected to influence politics and society. These include direct political impact through the implementation of recommendations and indirect political impact through civil society mobilization. Truth commissions may also have positive judicial impact by contributing to human rights accountability and negative judicial impact by promoting impunity. The article concludes that truth commissions do promote political and judicial change, albeit modestly, especially when human rights and victims’ groups pressure governments for policy implementation.